Identification of Number Sense Strategies used by Pre-service Elementary Teachers - (:unkn) unknown (My University, 2013)
The purpose of this study was to identify the use of number sense strategies by pre-service teachers studying at the department of elementary education. Compared to the previous one; new mathematics curriculum places more emphasis on various strategies such as estimation strategies, computational estimation strategies, rounding and mental computation, which are among the fundamental components of the number sense. The study was undertaken within the framework of the question "What strategies do the pre-service teachers, who will implement this curriculum, use while solving problems requiring number sense?". 133 pre-service teachers from the Elementary Education Department in a State University in the province of Istanbul participated in this study. "Number Sense Test" about five different number sense components was used as a testing instrument. Findings were analyzed with qualitative and quantitative methods. At the end of the research, pre-service teachers' number sense was found to be very low. When solution methods were analyzed, it was found that pre-service teachers preferred using "rule based methods" instead of "number sense" in each of the components. This finding was consistent with prior studies that show pre-service teachers' preference of written methods to number sense methods. With regard to research findings, suggestions were offered for future studies by emphasizing the necessity for measures to increase pre-service teachers' knowledge on number sense as well as its use. ©2013 Educational Consultancy and Research Center.
Keywords: Estimation; Number sense-based strategies; Partial number sense-based strategies; Pre-service elementary teachers